Association between bacteria other than Helicobacter pylori and the risk of gastric cancer. Issue 5 (15th July 2021) - Gunathilake, Madhawa; Lee, Jeonghee; Choi, Il Ju; Kim, Young‐Il; Kim, Jeongseon
Abstract: Background: The gastric microbiota, including Helicobacter pylori (HP), has a remarkable role in gastric cancer (GC) occurrence. Evidence for the role of non‐HP bacteria in GC risk is limited. We aimed to observe the association between bacteria other than HP and risk of GC in a Korean population. Methods: In this study, 268 GC cases and 288 healthy controls were included. Demographic data and total energy intake data were collected using a general questionnaire and a semiquantitative food frequency questionnaire, respectively. 16S rRNA gene sequencing was performed using DNA extracted from gastric biopsy samples. Results: Actinobacteria, Bacteroidetes, Firmicutes, Fusobacteria, and non‐HP Proteobacteria were the five main phyla in the gastric environment. The five phyla were negatively related to the relative abundance of Helicobacter species (all p < 0.001). The Shannon index, richness, and Pilou‐evenness were negatively correlated with Helicobacter species (all p < 0.001), while the microbial dysbiosis index was positively correlated with Helicobacter species ( p < 0.001). Participants with a higher relative abundance of Actinobacteria species showed a significantly increased risk of GC (OR: 3.16, 95% CI = 1.92–5.19, p‐trend<0.001). The non‐HP microbiota composition among the four groups (HP+cases, HP‐ cases, HP+controls, and HP‐ controls) was significantly different (ANOSIM R = 0.10, p = 0.001). Conclusion: Other than HP, several bacterial species might be associated with GC risk. HP status and GC status could determine the differences in microbial compositions. Further large prospective studies are warranted to confirm our findings.